Isolated Complete Distal Biceps Femoris Tendon Tears: Case Series and Literature Review - Azzopardi, Christine; Beale, David; James, Steven L.; Botchu, Rajesh (Indian Journal of Radiology and Imaging, 2021)
The Biceps femoris is a vital component of the posterolateral corner of the knee. We report two cases of isolated rupture of the biceps femoris, discuss the possible mechanism of injury, and review the literature.
Keywords: biceps femoris; tear; isolated